Now see the trees too - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
With a recent surge in forestry networks, it has been getting hard to see the wood from the trees lately. The Federation of forestry research institutions from 41 sub-Saharan African countries launched the Forestry Research Network for sub-Saharan...